Authority Of Non-Muslim Notary In Making Sharia Deeds - Aan Guswandi Arifin (PT. Anagata Sembagi Education, 2024)
This research discusses the urgency and regulation of sharia certification for notaries in making sharia deeds, as well as the implications of the use of foreign languages in such deeds. Shariah certification is identified as an important step to ensure notaries' competence in understanding the elements of shariah, although it is not yet a legal obligation. This certification is particularly relevant for non-Muslim notaries who may face obstacles in explaining the contents of sharia deeds that use Arabic and quotations from the Qur'an, in accordance with the requirements of Article 43 of the Law on Notarial Position (UUJN-P) which requires the deed to be made in Indonesian. This research highlights that the validity of sharia deeds is not determined by the religion or beliefs of the notary, but rather by the fulfillment of the formal and material requirements in accordance with Article 38 of the UUJN-P. Nonetheless, deeds that do not comply with Article 38 of UUJN-P are only considered as underhand deeds, with lower evidentiary power. Therefore, sharia certification is considered important to ensure that sharia deeds are made in accordance with established standards, although it does not determine the validity of the deed. This research also recognizes that the term 'non-Muslim notary' is not official and only appears in an academic context, given the absence of religious requirements in notary appointments under Article 3 of UUJN-P.